Integrating tsunami simulations in web applications using BROWNI, an open source client-side GPU-powered tsunami simulation library. (February 2022) - Galaz, J.; Cienfuegos, R.; Echeverría, A.; Pereira, S.; Bertín, C.; Prato, G.; Karich, J.C.
Abstract: Tsunami simulation software is a key component of state-of-the-art early warning systems but the inherent complexities in phases of installation, execution, pre and post-processing prevent their use in other areas of risk management such as communication and education. Recent advances in software and computational capacities such as the efficiency of GPU computing and the ubiquity of web browsers bring new opportunities to bridge the gap between expert and non-expert users. Here we present a Javascript library to enable a web browser to facilitate gathering and analyzing data from tsunami simulations, by means of interactive and efficient visualizations. At its core, the library uses WebGL, the browser's standard 3D graphics API, to run GPU accelerated computations of a tsunami model. A far-field tsunami model is implemented (linear shallow water equations discretized on spherical coordinates), and its implementation is validated against real tsunami observations, and benchmarked with two other tsunami software-packages. Two software platforms that use this library are presented to illustrate the powerful applications that can be developed for risk communication and education. These applications are characterized by their interactivity and fast computations, which enable users to focus on the understanding of the phenomena of tsunami propagation and iterate quickly to assess different scenarios and potential implications to tsunami risk management. Some limitations on this approach are discussed, in aspects such as scalability, performance, multi-threading and batch-processing, that can be relevant for other users. In our experience, the before mentioned benefits very well compensate the discussed limitations for this kind of applications. The library has an open source license, and is meant to be imported without modifying its source code to facilitate the creation of new applications as the ones herein presented. Highlights: BROWNI is a WebGL - Javascript tsunami simulation library. Simulations run on web browsers "out of the box" making users more proficient. Comparison with measurements and other simulators verify its accuracy. Scientific outreach and risk communication software made with BROWNI are described. Software and hardware limitations are discussed.